Biocatalysis and Nanotechnology - Grunwald, Peter (Boca Raton, FL : CRC Press, 2017)
"This book provides an actual overview of the various relations between nanotechnology and biocatalysis. Recently, nanobiocatalysis has rapidly developed to a subarea of enzyme biotechnology. It combines the advances in nanotechnology that have generated nanoscale materials of different sizes, shapes, and physicochemical properties, with the excellent characteristics of biocatalysts to an innovative technology. The book discusses the fabrication and application of these nanomaterials for the immobilization of enzymes for the sustainable production of goods and chemicals. Nanosupports are of advantage compared with bulk solid materials due to their high surface area resulting in a comparatively high enzyme loading and a significantly reduced mass transfer limitation. These characteristics are also of great use for applications in the fields of enzymatic biosensors, biofuel cells, bioelectronics, and photoelectrochemical analyte detection, where conductive nanomaterials improve the rate of electron transfer. Furthermore, nanostructured enzyme catalysis in organic solvents and its potential application for biodiesel production, probing of enzymatic activity, and identification of enzyme functions or inorganic nanoparticles as enzyme mimics together with an overview of nanotoxicology are also covered in this book."--Provided by publisher.
Chapter 1 Fundamentals of Nanotechnology -- chapter 2 Chapte 2. Biocatalysis: An Introduction -- chapter 3 Environmentally Benign Nanomaterial Synthesis Mediated by Culture Broths -- chapter 4 Rational Design of Enzyme{u2013}Polymer Biocatalysts -- chapter 5 Biological Strategies in Nanobiocatalyst Assembly -- chapter 6 Graphene-Based Nanobiocatalytic Systems -- chapter 7 Immobilization of Biocatalysts onto Nanosupports: Advantages for Green Technologies -- chapter 8 Enzyme Immobilization on Membrane and Its Application in Bioreactors -- chapter 9 Potential Applications of Nanobiocatalysis for Industrial Biodiesel Production -- chapter 10 Enzymogel Nanoparticles Chemistry for Highly Efficient Phase Boundary Biocatalysis -- chapter 11 Recent Advances in Nanostructured Enzyme Catalysis for Chemical Synthesis in Organic Solvents -- chapter 12 Probing Enzymatic Activity by Combining Luminescent Quantum Dots, Gold Nanoparticles, and Energy Transfer -- chapter 13 FRET Reporter Molecules for Identification of Enzyme Functions -- chapter 14 Quantum Dot Architectures on Electrodes for Photoelectrochemical Analyte Detection -- chapter 15 Inorganic Nanoparticles as Enzyme Mimics -- chapter 16 Enzyme Nanocapsules for Glucose Sensing and Insulin Delivery -- chapter 17 Nanostructured Materials for Enzymatic Biofuel Cells -- chapter 18 Enzymatic Biofuel Cells on Porous Nanostructures -- chapter 19 Nanoplasmonic Biosensors -- chapter 20 Enzyme Biocomputing: Logic Gates and Logic Networks to Interface and Control Materials -- chapter 21 Functional Nano-Bioconjugates for Targeted Cellular Uptake and Specific Nanoparticle{u2013}Protein Interactions -- chapter 22 Cell-Free Expression Based Microarrays: Applications and Future Prospects -- chapter 23 Overview of the Current Knowledge and Challenges Associated with Human Exposure to Nanomaterials.
OCLC-licensed vendor bibliographic record.
Keywords: SCIENCE -- Chemistry -- Industrial & Technical; TECHNOLOGY & ENGINEERING -- Material Science; Biocatalysis; Nanotechnology; Enzymes -- Biotechnology; Biotechnology -- Industrial applications